Acquired Carbapenem Resistance in Enterobacteria from UK Wastewater - Dickinson, Darren J D (2025)
Antimicrobial resistance (AMR) is rapidly becoming one of the greatest threats to modern healthcare around the world. The numbers of resistant infections have been rising rapidly over the last few decades, and mobile genetic elements (MGEs) carrying genes that confer resistance to our most valuable antibiotics have played a major role. Antimicrobial resistant bacteria are frequently isolated from wastewater treatment plants, and identification of their associated resistance genes and MGEs can be used to help understand the landscape of AMR in a local environment. The work described here investigated the presence of carbapenemase-producing Enterobacteriaceae (CPE) in wastewater from the UK East Midlands. Selective enrichment was used to isolate CPE as well as cephalosporin-resistant bacteria, phenotypic AMR profiles were determined by antimicrobial disc diffusion assay, and detection of beta-lactamase and plasmid genes was carried out using polymerase chain reaction (PCR). Nineteen isolates underwent whole genome sequencing, sixteen of which used Illumina and Oxford Nanopore Technologies sequencing technology to generate hybrid assemblies, which were used to investigate the genetic mechanisms of carbapenem resistance. CPE were identified from both wastewater influent and effluent, and those isolated were identified as Escherichia coli, Citrobacter portucalensis, Klebsiella pneumoniae, and Klebsiella quasipneumoniae, while a carbapenemase-producing Pseudomonas aeruginosa was also detected. Carbapenemase genes isolated in this work were blaNDM-4, blaNDM-5, blaOXA 181, blaIMP-7 and blaIMP-70, and these were found on IncF, IncX3, IncA/C and IncX3-ColKp3 plasmids. Sharing of highly related carbapenemase plasmids was seen across multiple sequence types, and in one case, across species, as an IncX3 plasmid was detected in E. coli and K. quasipneumoniae isolates. Analysis of results showed a greater proportion of NDM-producing E. coli were found in this work when compared to previous studies of carbapenemase-producing isolates from clinical and wastewater samples from the UK. Importantly, multidrug resistance regions were commonly associated with IS26 pseudo compound transposons, and experiments using clustered regularly interspaced short palindromic repeats(CRISPR)/CRISPR-associated protein 9 (Cas9)-based plasmid curing were able to show transposition of the genomic region containing blaNDM and other resistance genes from one plasmid to another. This study highlights the need for more surveillance of the spread of carbapenemase-producing organisms both locally and across the globe.